Challenges in the Accurate Use of Vocabulary Among Second-Language Learners - Yuluxi Yogeswaran; M.J.F Sujani; MB Nowzath; M.R Rishad Muhammed (Penerbit Hellow Pustaka, 2025)
Nowadays the vocabulary learning plays an important role in language teaching especially in the context where English is taught as a foreign language. This is because lexical competence is now seen a heart of language learning and the ultimate goal of language teaching is to improve the language competence of the learners. Additionally, vocabulary has been recognized as an important factor for language learning because insufficient vocabulary knowledge leads the learners to encounter difficulties in second language learning. Learners can significantly improve their language competence by developing their ability to use of vocabulary learning strategies. However, the present study primarily aimed at investigating how KM/KM/R.K.M.Girls’ Vidyalaya, students deals with vocabulary problems. Data was gathered for this study through Interview, Questionnaire and pre-test, post-test. Interviewing teachers and students and written assignment given to students. Individual attention was paid on the 20 samples from the pre-test marks. The average marks of the selected sample at the level were 50%. However, when the post-test had been it was 80%. These research finding are significant important since this will help the teachers to further their teaching methods and find ways to help students avoid marking error in subject-verb agreement. The result of this finding is the identification of difficulties in vocabulary learning and the possibilities to rectify them. The difficulties find outed were: Knowing the meaning of the vocabulary, Memorizing the spelling and writing with the correct spelling, Motivation in learning, The student’s talent in language, The student’s interest in vocabulary learning. Some suggestions and recommendations have been made to address this problem. They include giving sample exercises and practices to students, giving some teaching techniques to the teachers to be implemented in the classroom. All these efforts are meant for remedies to solve the problem in learning vocabulary in writing.